SANKSI HUKUM TERHADAP PERBUATAN LIWATH DENGAN ANAK DI BAWAH UMUR (Studi Perbandingan Undang-Undang Nomor. 35 Tahun 2014 tentang Perlindungan Anak dan Qanun Nomor 6 Tahun 2014 tentang Hukum Jinayat) - SAFINAH, SAFINAH (Petita : Jurnal Kajian Ilmu Hukum dan Syariah, 2016)
The purpose of this paper was to find out the provisions of the criminal act penalties of liwat (sodomy) against minors under the Act No. 35/2014 on the Protection of Children and the Qanun No. 6/2014 on the Jinayat (criminal acts) Law, and which was more effective between the Act and the Qanun on liwat case. Findings showed that the penalties within the Act No. 35/2014 included imprisonment of at least five (5) years and a maximum of 15 (fifteen) years, and a maximum fine of Rp 5,000,000,000.00 (five billion rupiah). Meanwhile, in addition to the penalties stipulated in the Act, the Jinayat Qanun No. 6/2014 further sentenced the offenders with a whip of at most 100 (one hundred) lashes or a maximum fine of 1,000 (one thousand) grams of pure gold or imprisonment for a maximum of 100 (one hundred) months. Of the two types of these punishments, both carried equal deterrent effects. However, flogging was seen to be more effective in terms of the psychological aspect. Keywords: Legal Sanctions, Homosexuality against Minors